2017
DOI: 10.1111/febs.14024
|View full text |Cite
|
Sign up to set email alerts
|

αβ′‐NAC cooperates with Sam37 to mediate early stages of mitochondrial protein import

Abstract: The mitochondrial proteome is mostly composed of nuclear-encoded proteins. Such polypeptides are synthesized with signals that guide their intracellular transport to the surface of the organelle and later within the different mitochondrial subcompartments until they reach their functional destination. It has been suggested that the nascent-polypeptide associated complex (NAC) - a cytosolic chaperone that recognizes nascent chains on translationally active ribosomes - has a role in the import of nuclear-encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…These proteins were selected firstly because they localize to different organelles and contribute to dissimilar activities: Rvb2 is a nuclear ATPase with helicase activity; Sky1 is a nuclear and cytoplasmic protein kinase, while Sam 37 is mitochondrial membrane component (46). Second, because some of these proteins perform multiple roles: Rvb2 contributes to the transcriptional regulation of ribosome biogenesis and ribonucleoprotein complex genes, to the assembly of box C/D snoRNP complexes (70–72) but also promotes RNA polymerase II assembly, DNA damage repair, telomerase complex assembly, mitotic spindle formation, the heat response and phosphatidylinositol three kinase related signaling (71–74), Sky1 regulates mRNA export, cation homeostasis, sulfur metabolism, mitophagy and apoptosis (74–77), while Sam37 is required for mitochondrial protein import (78,79). Third, because the e -values of these three interactors cover the entire range of our hit list (1.0E-02 to 1.0E-24; Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins were selected firstly because they localize to different organelles and contribute to dissimilar activities: Rvb2 is a nuclear ATPase with helicase activity; Sky1 is a nuclear and cytoplasmic protein kinase, while Sam 37 is mitochondrial membrane component (46). Second, because some of these proteins perform multiple roles: Rvb2 contributes to the transcriptional regulation of ribosome biogenesis and ribonucleoprotein complex genes, to the assembly of box C/D snoRNP complexes (70–72) but also promotes RNA polymerase II assembly, DNA damage repair, telomerase complex assembly, mitotic spindle formation, the heat response and phosphatidylinositol three kinase related signaling (71–74), Sky1 regulates mRNA export, cation homeostasis, sulfur metabolism, mitophagy and apoptosis (74–77), while Sam37 is required for mitochondrial protein import (78,79). Third, because the e -values of these three interactors cover the entire range of our hit list (1.0E-02 to 1.0E-24; Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Import factors at the surfaces of chloroplasts and mitochondria play a crucial role in the import of cargo by binding to incoming precursors associated with chaperones from the cytosol (Young et al, 2003;Smith et al, 2004;Qbadou et al, 2006;Ponce-Rojas et al, 2017). To test whether the import receptor AtToc159 is involved in specificity determination, we examined protein subcellular localization in ppi2 mutant protoplasts.…”
Section: Import Receptors Such As Attoc159 Specify Chloroplast Import When the Signal Sequence Can Deliver Clients To Both The Chloroplasmentioning
confidence: 99%
“…It was also demonstrated in yeast that OM14, a protein of the outer membrane of mitochondria, functions as a NAC receptor, and the knockout of its gene leads to a decrease in the proportion of ribosomes associated with the outer membrane of mitochondria, and to a disturbance of the import of proteins into the organelle [ 84 ]. Another mitochondrial protein, SAM37, a component of the yeast membrane protein sorting and assembly complex (SAM-complex), dynamically associated with the TOM translocon, was also reported to be a NAC partner [ 85 ].…”
Section: Translation Associated With the Outer Mitochondrial Membranementioning
confidence: 99%
“…In yeast, it has been observed that different NACs (heterodimers of αβ-NAC and αβ'-NAC) may be involved in the biogenesis of different sets of proteins through the binding of different substrates. The αβ'-NAC complex has a specific role in the biogenesis of mitochondrial proteins, since it is predominantly associated with ribosomes that actively synthesize these proteins [ 85 , 306 ].…”
Section: Peculiarities Of Localized Translation Regulationmentioning
confidence: 99%